COMPARATIVE STUDY OF PROCUREMENT PRACTICES: CENTRAL VS. LOCAL GOVERNMENT IN INDONESIA - Reynaldy Dwi Putra; Diana Sari (Jurnal Riset Terapan Akuntansi, 2026)
This study examines the differences in public procurement practices between the central and local governments in Indonesia, focusing on the legal framework, institutional capacity, and implementation effectiveness. The study aims to understand how decentralization affects procurement performance and governance quality across government levels. Using a descriptive-analytical approach and content analysis of official regulations, institutional reports, and international assessments, the research identifies disparities despite a unified regulatory framework. The central government achieves higher efficiency and compliance due to integrated digital systems and stronger institutional structures, while local governments face challenges related to infrastructure readiness, limited expertise, and inconsistent adherence to procedures. The novelty of this research lies in providing a comprehensive comparative analysis that combines regulatory, institutional, and technological dimensions of procurement governance, offering a broader understanding than previous studies that examined these aspects separately. The results show that capacity inequality and fragmented digital systems hinder uniform procurement performance nationwide. The study concludes that capacity-based procurement reform and institutional strengthening of regional procurement units are essential to achieve an equitable, transparent, and efficient procurement system. It recommends further research focusing on quantitative assessment of digital readiness and human resource capability to support sustainable public procurement governance in Indonesia. Keywords: : accountability, decentralization, efficiency, governance, procurement.